2018
DOI: 10.1002/rmb2.12101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mode of conception and depressive symptoms during the first 6 months post‐partum in Japan

Abstract: PurposeTo determine whether conventional treatment and assisted reproductive technology for infertility are associated with depressive symptoms and to identify the predictors of depressive symptoms during the first 6 months' post‐partum.MethodsA prospective cohort design was used, with the participants being recruited from 13 Japanese hospitals. Using self‐report questionnaires, a total of 2709 women (response rate: 71.9%) provided longitudinal data at five time points: during their hospital stay and at 1, 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…However, these findings indicated that pregnant women with a history of depression or depression during pregnancy might The current meta-analysis revealed that pregnant women giving birth to boys were at higher risk of PPD than women giving birth to girls. Previous studies supported our meta-analysis findings on the increased risk of PPD when pregnant women give birth to boys (Mori et al, 2018;Pampaka et al, 2019). However, one other meta-analysis of the sex of the baby and the risk of PPD showed that women giving birth to a girl was associated with a higher risk of developing PPD than those giving birth to a boy (Ye Furthermore, as Hall and Holden reported (Hall & Holden, 2008), they examined cognition, emotion and postnatal women's situation and found that mothers whose babies were boys had more negative appraisals.…”
Section: Risk Factors For Postpartum Depressionsupporting
confidence: 89%
“…However, these findings indicated that pregnant women with a history of depression or depression during pregnancy might The current meta-analysis revealed that pregnant women giving birth to boys were at higher risk of PPD than women giving birth to girls. Previous studies supported our meta-analysis findings on the increased risk of PPD when pregnant women give birth to boys (Mori et al, 2018;Pampaka et al, 2019). However, one other meta-analysis of the sex of the baby and the risk of PPD showed that women giving birth to a girl was associated with a higher risk of developing PPD than those giving birth to a boy (Ye Furthermore, as Hall and Holden reported (Hall & Holden, 2008), they examined cognition, emotion and postnatal women's situation and found that mothers whose babies were boys had more negative appraisals.…”
Section: Risk Factors For Postpartum Depressionsupporting
confidence: 89%
“…They observed that there was no significant association between the mode of conception and the depressive symptoms at any time point. 16 Similarly, a prospective cohort study done by Jane Fisher among 1,179 women in Australia through telephone interviews and self-report postal questionnaires found no association between mode of conception and postpartum depression. 17 A web-based study conducted by Pietro et al among 3,823 mothers observed that conception after IVF is not associated with maternal depressive symptoms during pregnancy or postpartum.…”
Section: Discussionmentioning
confidence: 97%
“…9 In our study, partner support was not significantly influencing the early postpartum depression as the immediate primary caregivers for mothers are better in Indian culture following delivery, whereas it might influence at a later part of the postpartum period where mothers are expected to return to their husband's family. 16,22 A study done by Tendais et al found no change in postpartum anxiety score between mothers who conceived spontaneously versus postinfertility treatment group with regard to multiple births of the baby. Our study is consistent with their result.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations